Active inclusion of people living with dementia in planning for dementia care and services in low- and middle-income countries. (February 2022) - Breuer, Erica; Freeman, Emily; Alladi, Suvarna; Breedt, Marinda; Govia, Ishtar; López-Ortega, Mariana; Musyimi, Christine; Oliveira, Déborah; Pattabiraman, Meera; Sani, Tara Puspitarini; Schneider, Marguerite; Swaffer, Kate; et al.
Involving people living with dementia in service design and planning has become more common in high-income countries. It remains rare in low- and middle-income countries where two-thirds of the world's people with dementia live. In this commentary article, we explore the barriers to inclusion of people living with dementia in planning in low- and middle-income countries and make a case for the inclusion of people living with dementia in care and service planning. We suggest how this can be done at individual, community or national and state level using the following principles: 1) respecting the rights of people living with dementia to self-determination; 2) valuing people living with dementia's unique understanding of dementia; 3) creating a culture of active inclusion which creates a space for people living with dementia to participate and 4) ensuring appropriate accommodations are in place to maximise participation.